A randomised controlled trial of a family-group cognitive-behavioural (FGCB) preventive intervention for the children of parents with depression: short-term effects on symptoms and possible mechanisms - Löchner, Johanna; Starman-Wöhrle, Kornelija; Takano, Keisuke; Engelmann, Lina; Voggt, Alessandra; Loy, Fabian; Bley, Mirjam; Winogradow, Dana; Hämmerle, Stephanie; Neumeier, Esther; Wermuth, Inga; Schmitt, Katharina; et al. (Child and Adolescent Psychiatry and Mental Health, 2021)
Objective: Parental depression is one of the biggest risk factors for youth depression. This parallel randomized controlled trial evaluates the effectiveness of the German version of the family-group-cognitive-behavioral (FGCB) preventive intervention for children of depressed parents. Methods: Families with (i) a parent who has experienced depression and (ii) a healthy child aged 8–17 years (mean = 11.63; 53% female) were randomly allocated (blockwise; stratified by child age and parental depression) to the 12-session intervention (EG; n = 50) or no intervention (CG; usual care; n = 50). Self-reported (unblinded) outcomes were assessed immediately after the intervention (6 months). We hypothesized that CG children would show a greater increase in self-reported symptoms of depression (DIKJ) and internalising/externalising disorder (YSR/CBCL) over time compared to the EG. Intervention effects on secondary outcome variables emotion regulation (FEEL-KJ), attributional style (ASF-KJ), knowledge of depression and parenting style (ESI) were also expected. Study protocol (Belinda Platt, Pietsch, Krick, Oort, & Schulte-Körne, 2014) and trial registration (NCT02115880) reported elsewhere. Results: We found significant intervention effects on self-reported internalising (ηp2 = 0.05) and externalising (ηp2 = 0.08) symptoms but did not detect depressive symptoms or parent-reported psychopathology. Parental depression severity did not modify these effects. Both groups showed equally improved knowledge of depression (ηp2 = 0.06). There were no intervention effects on emotion regulation, attributional style or parenting style. Conclusion: The German version of the FGCB intervention is effective in reducing symptoms of general psychopathology. There was no evidence that the mechanisms targeted in the intervention changed within the intervention period.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Family intervention; High-risk; Parental depression; Prevention of depression